International Business Finance : Multinational Corporation - Abdul Rohim; Dwi Nur Farah; Hesty Nurlita Fauzia; M Nofal Abdillah; Muhammad Ilzam Firdaus (Journal of Islamic Economics and Finance, 2025)
This study examines the role of multinational corporations (MNCs) in the context of international business finance, focusing on the reasons for overseas expansion and the globalization of financial products and markets. The discussion includes strategic, operational, and financial motivations that drive companies to expand internationally. In addition, this study analyzes the impact of global financial market integration on MNCs' cross-border activities. The study concludes that global expansion and market globalization provide MNCs with opportunities to increase efficiency, reach new markets, and manage risk more optimally in an interconnected economy.